From myth to tale: a transformation of the supernatural characters in the scandinavian folklore - Shpakouskaya, Nina G. (Journal of the Belarusian State University. Philology, 2019)
Scandinavian fairy tales are analyzed in this article in order to define a difference between how the supernatural characters (giants, trolls, elves and dwarfs) are described in the Scandinavian fairy tales and the Norse mythology. During the analysis, it is argued that a difference among various supernatural characters vanishes to large extent in fairy tales. It is concluded that a transformation of the mythological creatures into the fairy ones is based primarily on extension of their connotation by adding a metaphorical meaning aimed at expression of social contradictions.
Keywords: Scandinavian fairy tales; Scandinavian mythology; Poetic Edda; Scandinavian folklore; giant; troll; dwarf; elf